2014
DOI: 10.4315/0362-028x.jfp-13-479
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxigenic Bacillus cereus Strains Isolated from Vegetables in Mexico City

Abstract: Bacillus cereus can cause diarrhea and emetic syndromes after ingestion of food contaminated with it. This ability is due to the production of enterotoxins by this microorganism, these being the hemolysin BL complex, which is involved in the diarrheal syndrome, and cereulide, which is responsible for the emetic syndrome. The detection of genes associated with the production of these toxins can predict the virulence of strains isolated from contaminated food. In this paper, we analyzed 100 samples of vegetables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
6
12
5
1
Order By: Relevance
“…The results of detection of strains of the B. cereus species by the presence of the nhe A gene in the studied plant products are shown in Table 3. Comparing the results with those given for vegetables from the city of Mexico, it is possible to note practically the same trends of detection of B. cereus for most types of fresh vegetable raw materials -61.8% and 57% for the Ukrainian and Mexican regions, respectively [29]. And as noted by Valero et al [30] in Spain, all samples of fresh raw materials -peppers, cucumbers, tomatoes, carrots, zucchini, onions -were contaminated with B. cereus.…”
Section: Pcr Detection Of B Cereus In Food Samplessupporting
confidence: 61%
“…The results of detection of strains of the B. cereus species by the presence of the nhe A gene in the studied plant products are shown in Table 3. Comparing the results with those given for vegetables from the city of Mexico, it is possible to note practically the same trends of detection of B. cereus for most types of fresh vegetable raw materials -61.8% and 57% for the Ukrainian and Mexican regions, respectively [29]. And as noted by Valero et al [30] in Spain, all samples of fresh raw materials -peppers, cucumbers, tomatoes, carrots, zucchini, onions -were contaminated with B. cereus.…”
Section: Pcr Detection Of B Cereus In Food Samplessupporting
confidence: 61%
“…While one study has reported presence of hblACD genes in all 70 tested isolates from ready-to-eat vegetables in South Korea [ 36 ], another study has found one or more hbl genes in 23.5 – 70.6 % of B. cereus group isolates from food products in Brazil [ 44 ]. The hblA has been detected in all 57 B. cereus isolates from raw vegetable samples collected in Mexico City [ 45 ]. While hblA and hblD have been detected in 72 % B. cereus isolates ( n = 88) from retail spices in USA, hblC has been detected in 71 % of these isolates [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of hblACD genes in all 70 tested isolates from ready-to-eat vegetables in South Korea, detection of one or more hbl genes in 23.5-70.6% of B. cereus group isolates from food products in Brazil, detection of hblA in all 57 B. cereus isolates from raw vegetable samples collected in Mexico City, detection of hblA and hblD in 72% of B. cereus isolates from retail spices in the USA, hblC in 71% of these isolates are noted in the literature and testify to the relevance of such studies [45,[47][48][49][50].…”
Section: Molecular Genetic Methods Of Microbiological Control Of Regumentioning
confidence: 88%
“…Modern works of a number of foreign researchers have shown that bacillary microorganisms synthesize genes that cause the ability of B. cereus to cause diarrheal and emetic syndromes [44][45][46][47]. B. cereus causes diarrhea and emetic syndromes, producing various extracellular toxins, including the three main types of enterotoxins, namely hemolysin BL (hbl), nonhemolytic enterotoxin (nhe) and cytotoxin K (cyt K) [48].…”
Section: Molecular Genetic Methods Of Microbiological Control Of Regumentioning
confidence: 99%